Peran Manajemen Gereja Terhadap Kaum Disabilitas dan Akses Ke Dalam Pelayanan Gereja - Tataung, Jurdila Angelia (Jurnal Ilmiah Wahana Pendidikan, 2024)
People with disabilities have not been given a proper place in church stewardship. Marginalization of people with disabilities can be caused by stigmatization of their abilities. This paper intends to explain the congregation's understanding of people with disabilities and how the church empowers people with disabilities and Church management is needed in terms of services to achieve the set goals, therefore management must exist and be made as well as possible to be implemented. The research method used is descriptive qualitative. The results of this study found that people with disabilities were initially difficult to accept their circumstances. However, they can rise and think positively because they get assistance from the church